Pengaruh Religiusitas terhadap Kehamilan Pada Masyarakat Hindu Etnis Bali Di Desa Mantaren II Kecamatan Kahayan Hilir Kabupaten Pulang Pisau - Lestarina, Lestarina; Astawa, I Nyoman Sidi (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
Religiosity is currently an aspect of human life that has become one of the main topics in studies or research conducted by experts or scientists in various fields. Previous studies have not examined religiosity and pregnancy in Balinese ethnic Hindu communities in transmigration areas. This study aims to explore and understand the influence of religiosity on pregnancy in Balinese ethnic Hindu communities in Mantaren II village, Kahayan Hilir sub-district, Pulang Pisau Regency, Central Kalimantan Province. This research uses a qualitative phenomenological method approach. Data were collected using semi-structured interviews and analysed by condensation, display and verification. Religiosity has an influence in life related to pregnancy that occurs in the Balinese ethnic Hindu community that has been married as seen from the existence of various activities and actions when the wife in the family is experiencing pregnancy such as praying, praying, offering offerings, and carrying out ceremonies for pregnancy.